Edpuzzle as a Learning Medium to Improve Students’ Listening Comprehension - M. Fikri Nugraha Kholid (JEIT (Journal of Educational Innovations and Technologies), 2025)
Listening comprehension is a foundational component of English language proficiency, yet many junior high school EFL learners struggle when instruction relies primarily on teacher-centered, audio-only practices. This study investigated whether the use of Edpuzzle, an interactive video-based platform with embedded questions, significantly improves students’ listening comprehension. A quasi-experimental pre-test/post-test design was implemented with two intact seventh-grade classes at SMPN 1 Jatimulyo (experimental n = 32; control n = 32) during the 2025/2026 academic year. Students completed a listening comprehension test before and after three instructional sessions. Descriptive statistics indicated that the experimental group improved from M = 78.91 (SD = 12.49) to M = 85.94 (SD = 10.73), while the control group improved from M = 69.69 (SD = 8.61) to M = 78.59 (SD = 8.64). Because at least one distribution did not meet the normality assumption, between-group differences were tested using the Mann-Whitney U test, which showed a statistically significant difference in post-test scores (U = 308.00, Z = -2.77, p = .006). The findings suggest that integrating interactive video through Edpuzzle can enhance learner engagement and support listening outcomes in EFL classrooms.